Secondary Organic Aerosol Formation Mechanism by Heterogeneous Reaction of Isoprene with OH Radical: A Theoretical Study - Zhang, Chenxi; Sun, Xiaomin; Wang, Wenxing (Asian Journal of Chemistry, 2011)
The comprehensive mechanism of OH-isoprene system is reported. The profile of the potential energy surface was constructed and all of the possible channels were discussed. Geometries have been optimized at the B3LYP level with the 6-31+G** basis set. Part single-point energy calculations have been carried at the QCISD(T)/6-31+G** or B3LYP/6-311++G(3df,2pd) level. Some polyols, for example 2-methylbutanetetraol, are identified, which are easy to take place the aerosol-phase heterogeneous chemical reactions in the formation of secondary organic aerosol. Physical properties such as heats of formation, standard entropies, Gibbs free energies of formation and solvation energies are determined using quantum mechanics method. The quantum mechanics results are used to calculate the equilibrium distributions of the available minima and the equilibrium constants (reported as log K) of aerosol-phase chemical reactions both in gas-phase and aqueous-phase. The results of quantum mechanics calculations are potentially useful in determining the relative thermodynamic tendency for atmospheric aerosol-phase reactions.